2022
DOI: 10.3390/covid2030017
|View full text |Cite
|
Sign up to set email alerts
|

Forecast of Omicron Wave Time Evolution

Abstract: The temporal evolution of the omicron wave in different countries is predicted, upon adopting an early doubling time of three days for the rate of new infections with this mutant. The forecast is based on the susceptible–infectious–recovered/removed (SIR) epidemic compartment model with a constant stationary ratio k=μ(t)/a(t) between the infection (a(t)) and recovery (μ(t)) rates. The assumed fixed early doubling time then uniquely relates the initial infection rate a0 to the ratio k; this way the full tempora… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 37 publications
(50 reference statements)
0
5
0
Order By: Relevance
“…with constants q 0 , q 1 and G. The fatality rate (168) starts from the constant value q 0 and decreases with the typical time scale G −1 to its final constant value q 1 . Such a behavior accounts well for the COVID-19 omicron which had a much smaller (about an order of magnitude) fatality rate than the earlier mutants [22] occurring about a year earlier. Such a slow gradual decrease is well captured by the adopted fatality rate (168) in the case G b 0 < 1, allowing us the linear approximation…”
Section: Gradually Decreasing Fatality Ratementioning
confidence: 53%
See 1 more Smart Citation
“…with constants q 0 , q 1 and G. The fatality rate (168) starts from the constant value q 0 and decreases with the typical time scale G −1 to its final constant value q 1 . Such a behavior accounts well for the COVID-19 omicron which had a much smaller (about an order of magnitude) fatality rate than the earlier mutants [22] occurring about a year earlier. Such a slow gradual decrease is well captured by the adopted fatality rate (168) in the case G b 0 < 1, allowing us the linear approximation…”
Section: Gradually Decreasing Fatality Ratementioning
confidence: 53%
“…The main difference between the SIRVD and the SIRV model is the discrimination between recovered and deceased persons by introducing two different compartments. This is necessary as the omicron mutant the COVID-19 has a much smaller (about an order of magnitude) fatality rate than earlier mutants [22]. This gradually changing fatality rate is not accompanied by a corresponding change in the time dependence of the recovery rate.…”
mentioning
confidence: 99%
“…The projected mortality was between 60% of the Delta wave, while hospitalization was projected to be comparable to the situation in January 2021 to 4–5 times higher in the most pessimistic scenario ( 13 ). On the basis of these observations, the Omicron variant was projected to peak in approximately 32–45 days, ( 14 ) therefore, reaching a peak by the end February in Indonesia.…”
Section: Epidemiologymentioning
confidence: 98%
“…Among them, Cai et al [ 24 ] reported that the cancellation of the dynamic zero-COVID policy would trigger a wave of infections in Omicron, causing about 1.55 million deaths. Schlickeiser et al [ 25 ] predicted deaths in the UK, Switzerland and Germany using the SIR epidemic compartment model. Muniyappan et al [ 26 ] dealt with the mathematical modeling of the second wave of COVID-19 and verified the current Omicron variant pandemic data in India.…”
Section: Introductionmentioning
confidence: 99%